Determinants of perceived need for dental pain medication - Pau A, Croucher R, Marcenes W (Journal compilation, 2008)
To describe the perceived inability to cope (PIC) and impact on quality of life (QOL) in dental pain patients, and investigate their effect on perceived need for pain medication.